Geography education research in Indonesia: retrospect and prospect - Dwi Angga Oktavianto (Universitas Negeri Malang, 2020)
Geography Education Research has long been part of the development of Geography in Indonesia. So far there has been no research on the condition of Geography Education Research in Indonesia. This study explores articles about Geography Education Research that are sourced from journals produced by departments or faculties of Geography in Indonesia and have been indexed by SINTA. The results of the exploration are then analyzed to retrospect the research that has been done and try to look at the prospects of future geography education research.